Kichwa Interference in the English learning process in ninth year basic education at Delia Ibarra de Velasco Educative Unit school year 2020 - 2021 - Muente Núñez, Margarita Patricia (2021)
Morphology is one of major components of Linguistics that studies how words are formed, the rules for combining them, their inflections and their relationship to other words in the same language. It studies the structure of words and parts of words such as root words, stems, prefixes and suffixes; due to, the research’s aim is to identify the most relevant morphological interferences between Kichwa as a mother tongue and English as a foreign language; in Ninth Year of Basic Education at Delia Ibarra de Velasco Educative Unit school year 2020-2021 (Pujilí- Ecuador). The design was qualitative, in order to distinguish the fundamental aspects which are focus on people’s points of view, previous knowledge about the literature of this study, in the other hand, the co-relational method was used because it analyzed the relation between the morphological similarities and differences between Kichwa and English in order to know what linguistics difficulties face in the English learning process. The results of the survey applied to 50 Kichwa speakers, divided into the experimental and control group, demonstrated that Kichwa interference in the students´ English writing since they tend to adopt the structure of their native language can correlate with some English morphological structures it was also evident that they can be strengths during the English learning process. The investigator designed worksheets with exercises aimed to use the morphological similarities. Consequently, the researcher proposes to use the handbook to teach English to a Kichwa speaker since there is no academic material related to the main aim of this research which is the morphological contrast between both languages